Lab marks automation system - Chuah Lee Kien (Universiti Malaysia Perlis, 2008)
Lab Marks Automation System is a system where have one device name as WiDSTAC (Wireless Data Storage and Acquisition) that is used by lecturers or lab tutor to key in student’s mark and also can view back the mark that been saved inside the system. The system is using wireless connection. For hardware part, it uses LCD, Keypad, RF module, microcontroller 8051, MAX 232, TIP 31C, transistor BC547 and power regulator. In software part, it is using programming 8051, Microsoft Access and Visual Basic use to make interface program to display the lab marks result. Microsoft Access used to save the data and keep it as database. This system work in half duplex transmission where just one transmission in a moment. In the menu of WiDSTAC there is 2 function that user can choose either ‘Add’ function or ‘Find’ function. ‘Add’ function is to key in student marks to system. ‘Find’ function is to call the exited marks to display it. Mark statistic for total students, lower mark, higher mark and graph ( Mark Versus Table Number) in one group of lab will display in Visual Basic’s application. This system is successfully works as mention like above.